Pregnancy Outcome following Prenatal Diagnosis of Chromosomal Anomaly: A Record Linkage Study of 26,261 Pregnancies. - Myrthe Jacobs; Sally-Ann Cooper; Ruth McGowan; Scott M Nelson; Jill P Pell (PLoS ONE)
Previous studies have demonstrated the influence of changes in the age at which women give birth, and of developments in prenatal screening and diagnosis on the number of pregnancies diagnosed and terminated with chromosomal anomalies. However, we are unaware of any population studies examining pregnancy terminations after diagnosis of chromosomal anomalies that has included all aneuploidies and the influence of maternal factors. The aims of this study were to examine the association between results of prenatal tests and pregnancy termination, and the proportion of foetuses with and without chromosomal anomalies referred for invasive diagnostic tests over time. Diagnostic information of 26,261 prenatal invasive tests from all genetic service laboratories in Scotland from 2000 to 2011 was linked to Scottish Morbidity Records to obtain details on pregnancy outcome. Binary logistic regression was carried out to test the associations of year and type of diagnosis with pregnancy termination, while controlling for maternal age, neighbourhood deprivation and parity. There were 24,155 (92.0%) with no chromosomal anomalies, 1,483 (5.6%) aneuploidy diagnoses, and 623 (2.4%) diagnoses of anomaly that was not aneuploidy (including translocations and single chromosome deletions). In comparison with negative test results, pregnancies diagnosed with trisomy were most likely to be terminated (adjusted OR 437.40, 95% CI 348.19-549.46) followed by other aneuploid anomalies (adjusted OR 95.94, 95% CI 69.21-133.01). During the study period, fewer pregnancies that were diagnosed with aneuploidy were terminated, including trisomy diagnoses (adjusted OR 0.44, 95% CI 0.26-0.73). Older women were less likely to terminate (OR 0.35, 95% CI 0.28, 0.42), and parity was also an independent predictor of termination. In keeping with previous findings, while the number of invasive diagnostic tests declined, the proportion of abnormal results increased from 6.09% to 10.88%. Systematic advances in prenatal screening have improved detection rates for aneuploidy. This has been accompanied by a reduction in the rate of termination for aneuploidy. This may reflect societal changes with acceptance of greater diversity, but this is speculation, and further research would be needed to test this.